Internet of things based automated agriculture system for irrigating soil - Md. Golam Kibria; Mohamad Tarmizi Abu Seman (Institute of Advanced Engineering and Science, 2022)
This work describes the design of an internet of things (IoT)-based prototype system for outdoor agriculture farmland that employs low-cost sensors for detecting basic agriculture parameters such as soil moisture level, air temperature, and air humidity to irrigate the farmland automatically and manually while tracing the water volume. Therefore, since the water requirement varies according to plant type and plant growth stages, this research focuses on a feature where user can adjust the soil moisture level from software according to the plant type and age stages so that a suitable moisture level can be maintained for plants. Apart from that, the system also has a feature to adjust the temperature threshold limit from the application software so that when the temperature sensor value exceeds the respective threshold limits, it sprinkles the water for a limited time so that plants are not damaged due to overheating. Google sheets is used for cloud storage, and Wi-Fi is used to send data to the cloud using the HTTP protocol. The Blynk application software is used to monitor and control purposes.